Evaluation of parameters for high efficiency transformation of acinetobacter baumannii - Yıldırım, Süleyman; Thompson, Mitchell; Jacobs, Anna; Zurawski, Daniel; Kirkup, Benjamin (Nature Publishing Group, 2016)
Acinetobacter baumannii is an emerging, nosocomial pathogen that is poorly characterized due to a paucity of genetic tools and methods. While whole genome sequence data from several epidemic and environmental strains have recently become available, the functional characterization of genes is significantly lagging. Efficient transformation is one of the first steps to develop molecular tools that can be used to address these shortcomings. Here we report parameters allowing high efficiency transformation of A. baumannii. Using a multi-factorial experimental design we found that growth phase, voltage, and resistance all significantly contribute to transformation efficiency. The highest efficiency (4.3 x 10(8) Transformants/mu g DNA) was obtained at the stationary growth phase of the bacterium (OD 6.0) using 25 ng of plasmid DNA under 100 Ohms resistance and 1.7 kV/cm voltage. The optimized electroporation parameters reported here provide a useful tool for genetic manipulation of A. baumannii.
WOS: 000370802200001
PubMed ID: 26911658